Anti-High Mobility Group Box 1 Neutralizing-Antibody Ameliorates Dextran Sodium Sulfate Colitis in Mice - Chen, Liping; Li, Junhua; Ye, Zhenghao; Sun, Binghua; Wang, Lu; Chen, Yu; Han, Jian; Yu, Meiping; Wang, Ying; Zhou, Qi; Seidler, Ursula; Tian, De’an; et al. (Frontiers in Immunology, 2020)
High mobility group box 1 (HMGB1) is a ubiquitous nuclear protein in mammals. When released into the extracellular space, it acts as a damage-associated molecular pattern. This study investigates whether increased HMGB1 levels are found in the intestinal mucosa of ulcerative colitis (UC) patients, and whether an anti-HMGB1 neutralizing-antibody (HnAb) can inhibit the intestinal inflammation elicited by dextran sulphate sodium (DSS) in mice. Because toll-like receptor 4 (TLR4) is implicated in HMGB1-mediated immune cell activation, DSS colitis was also elicited in TLR4-deficient mice in the presence and absence of HnAb. The expression of HMGB1 in UC patients was examined. HnAb was administered via intraperitoneal injection to TLR4 deficient mice and their wild-type littermates, both being induced to colitis with DSS. Finally, the protective effect of HnAb and TLR4 deficiency were evaluated. In UC patients, HMGB1 was up-regulated in the inflamed colon. When administered during DSS application, HnAb alleviated the severity of colitis with a lower disease activity index, limited histological damages and reduced production of proinflammatory cytokines. This antibody also limited colonic barrier loss, decreased colonic lamina propria macrophages and partially reversed the DSS treatment-associated dysbiosis. The protective effect of this antibody was enhanced in TLR4-deficient mice in some aspects, indicating that both additional HMGB1-mediated as well as TLR4-mediated inflammatory signaling pathways were involved in the induction of colitis by DSS. HnAb ameliorated colitis via macrophages inhibition and colonic barrier protection. It may therefore be a novel treatment option in colitis.